People Copy Success More Than Failure in Social Learning - Xianwei Meng; Junichi Oishi; Minori Onishi; Momoka Sakaguchi; Sota Yabushita; Yasuhiro Kanakogi (SAGE Open, 2024)
Social learning is a fundamental mechanism for efficiently transferring and coordinating norms, skills, and sophisticated cultural information to individuals. However, the psychological mechanisms underlying social learning remain unclear. To investigate this, we recruited adult participants ( N  = 103), who observed a model’s performance in a two-choice reward-searching task. Two cues were used to determine the reward, with both cues possessing an alternative signal that had a specific rule for finding the reward. Although the model succeeded with one cue but failed with another, both possessed equal information, which enabled the participants to find the reward. Participants were more likely to use the cue linked to the model’s success than the model’s failure when asked to solve the task by themselves. This “copy success” bias reflects the psychological process underlying social learning suggested by previous evolutionary theories and provides practical suggestions for efficient learning processes.